2009
DOI: 10.1260/0309-524x.33.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulations of Wind Speed Data

Abstract: A new Monte Carlo simulation procedure and nearby regional weather station data are used to predict wind speed and turbine energy. The evaluation of the predication values used cumulative distribution function (CDF) graphs. The predication process employed Weibull shape and scale values developed from 1, 12, 20 and 24 years of record for each weather station. Simulation using one year of wind speed data of a weather station located downwind of the wind turbine site resulted in the greatest match of simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Others have looked at improving AEP forecasting using Monte–Carlo simulations (Gallagher and Elmore, 2009; Hrafnkelsson et al, 2016). This method improved the forecast of wind turbines over normal Weibull distributions because it accounted for seasonal variations and autocorrelations of wind speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Others have looked at improving AEP forecasting using Monte–Carlo simulations (Gallagher and Elmore, 2009; Hrafnkelsson et al, 2016). This method improved the forecast of wind turbines over normal Weibull distributions because it accounted for seasonal variations and autocorrelations of wind speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been used to generate synthetic wind data with hourly timesteps. Kaminsky et al 7 present and compare several such methods including independent and identically distributed values [8][9][10][11][12] one-or two-step Markov chain models, [13][14][15][16] Box-Jenkins or auto-regressive (moving average) (AR(MA)) models, 17 which have been used for synthetic wind speed data, 18 and Markov chain models. 7 They pointed out that most methods lack lower frequency information, i.e., diurnal effects are typically neglected even though autocorrelation for several hours may be included.…”
Section: B Synthetic Wind Speed Data In Energy Modellingmentioning
confidence: 99%
“…A new Monte Carlo simulation procedure and nearby regional weather station data are used to predict wind speed and turbine energy. The results indicated that the replacement of on-site wind data can replace provide accurate predictions of proposed nearby wind turbine [5]. Another computational model using one year of wind speed data of a weather station located downwind of the wind turbine site resulted in the greatest match of simulation results to the measured values.…”
Section: Introductionmentioning
confidence: 97%